Phytochemical screening and evaluation of in vitro antioxidant, antibacterial and antibiofilm activities of Mitragyna speciosa leaf extract - Begum, Taslima; Ahmed, Qamar Uddin; Arzmi, Mohd Hafiz; Helal Uddin, A.B.M.; Khatib, Alfi; Syed Mohamad, Sharifah Nurul Akilah; Syed Nasarudin, Syarifah Nurhikmah Izzati; Abbas, Syed Atif; Abd Aziz, Zul Hadif (Institut Kimia Malaysia, 2025)
Mitragyna speciosa leaves have long been utilised in traditional Southeast Asian medicine, including in Malaysia, for treating ailments such as diarrhoea, intestinal infection and wound healing. In light of the global rise in antibiotic resistance, this study aimed to explore the phytoconstituent composition, antioxidant capacity, antibacterial and antibiofilm properties of M. speciosa leaf extract. A 100% methanol extract was prepared using maceration (referred to as 100% M) and subjected to comprehensive phytochemical screening, antioxidant assays, antibacterial and antibiofilm evaluations, and Q-ToF-LCMS analysis. The extract demonstrated high levels of bioactive constituents, with a total phenolic content (TPC) of 257.46 ± 1.32 mg gallic acid equivalent/g of extract and a total flavonoid content (TFC) of 50.75 ± 0.24 mg quercetin equivalent/g of extract. Antioxidant activity was notable, with DPPH IC50 of 7.94 ± 0.12 µg/mL and FRAP values of 2103.46 ± 5.67 mg ascorbic acid equivalent/g of extract. Antibacterial testing revealed strong activity against Staphylococcus aureus (zone of inhibition [ZOI] at 100 mg/mL: 9.89 ± 0.10 mm; MIC: 5 mg/mL), and Streptococcus mutans (ZOI at 100 mg/mL: 7.22 ± 0.19 mm; MIC: 10 mg/mL). The extract also showed significant antibiofilm activity with % inhibition ranging from 88.68 ± 0.40 to 93.96 ± 0.33 against S. aureus, and 22.97 ± 1.28 to 40.62 ± 2.11 against S. mutans. Q-ToF-LCMS analysis identified a diverse array of phenolic, flavonoid, terpenoids, alkaloid and other types of compounds, which likely contribute to the observed biological activities. These findings suggest that M. speciosa leaves methanol extract holds promise as a source of novel antibacterial agents, supporting its traditional use and potential for pharmaceutical development.